2006
DOI: 10.1111/j.1365-2516.2006.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Total joint replacement in patients with inhibitors

Abstract: Today, total joint replacement is the treatment of choice for chronic haemophilic arthropathy of the knee and hip in developed and developing countries. After the last World Haemophilia Congress and Musculoskeletal Congress, we cannot say the same for haemophilic patients with inhibitors because elective surgery today is still limited to few centres and extremely few patients. This is because until the first half of the 1990s, performing surgery in haemophilic patients with inhibitors was associated with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 23 publications
2
36
0
4
Order By: Relevance
“…They found that most bleeding complications could be resolved by increasing the rFVIIa dose or administering an extra dose and concluded that the optimal initial rFVIIa bolus dose for orthopedic surgery may be higher than 90 μg/kg. Furthermore, in the major orthopedic interventions reported by Solimeno et al23 and Rodriguez-Merchan et al,24 bleeding complications were only observed in patients receiving the dose of 90 μg/kg rFVIIa. Based on these data, a minimum initial dose of 120 μg/kg rFVIIa, followed by a similar or 90 μg/kg dose every 2 hours, was suggested for patients in the BI group 22…”
Section: Discussionmentioning
confidence: 92%
“…They found that most bleeding complications could be resolved by increasing the rFVIIa dose or administering an extra dose and concluded that the optimal initial rFVIIa bolus dose for orthopedic surgery may be higher than 90 μg/kg. Furthermore, in the major orthopedic interventions reported by Solimeno et al23 and Rodriguez-Merchan et al,24 bleeding complications were only observed in patients receiving the dose of 90 μg/kg rFVIIa. Based on these data, a minimum initial dose of 120 μg/kg rFVIIa, followed by a similar or 90 μg/kg dose every 2 hours, was suggested for patients in the BI group 22…”
Section: Discussionmentioning
confidence: 92%
“…Due to an excellent response of our patient to a 90 µg/kg dose of rFVIIa, we did not consider the initially recommended dose of 270 µg/kg (9). Solimeno et al reported that a high responder patient had a 1 BU/ml antibody titer at the time of surgery; a high dose of factor VIII (52000 U) was used for the first five days and on the fifth day after surgery, rFVIIa was administered for two days (6). In our case, the patient’s inhibitor titer was below 1 BU/ml before surgery, and we controlled his bleeding during and after surgery with a high dose of FVIII.…”
Section: Discussionmentioning
confidence: 99%
“…Such cases represent a major therapeutic challenge to clinicians (5). Arthroplastic surgery in hemophilic patients having such inhibitors remains a rare, expensive, and difficult surgery, whose management represents a significant challenge (6). Since 1988, recombinant activated factor VII (rFVIIa) have been indicated for use in surgical prophylaxis, as well as for the treatment of bleeding episodes, in patients with hemophilia and high-responding inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…They found that most bleeding complications could be resolved by increasing the rFVIIa dose or administering an extra dose and concluded that the optimal initial rFVIIa bolus dose for orthopedic surgery may be higher than 90 µg/kg. Furthermore, in the major orthopedic interventions reported by Solimeno et al 23 and Rodriguez-Merchan et al, 24 bleeding complications were only observed in patients receiving the dose of 90 µg/ kg rFVIIa. Based on these data, a minimum initial dose of 120 µg/kg rFVIIa, followed by a similar or 90 µg/kg dose every 2 hours, was suggested for patients in the BI group.…”
Section: Dose Evaluationmentioning
confidence: 99%
“…15 The considerable heterogeneity in the assessment of hemostatic efficacy and in sampling time points is in agreement with reports from nonrandomized studies. 10,[22][23][24][25][32][33][34][37][38][39] Obviously, this constitutes a significant problem for the interpretation and comparison of results from the studies of patients with hemophilia. Thus, data interpretation and the comparison of efficacy in the future studies on patients with hemophilia would be improved if efficacy parameters were standardized.…”
Section: Treatment Efficacy Evaluationmentioning
confidence: 99%